How Shari’ah Addressed Environmental and Social Responsibility Issues - Dr. Hashem Osamah Yahya Mohammed; Tawfik Abdulrahman Alqasemi (Academy of Creativity Sama for Studies, Consultations, and Scientific Development, 2025)
Non-Indexed Publication